PS-BPP02-3: FACTORS FOR NEW-ONSET ISOLATED DIASTOLIC HYPERTENSION AND PROGRESSION TO SYSTOLIC HYPERTENSION IN JAPAN. (January 2023) - Sakoda, Takashi; Akasaki, Yuichi; Kawasoe, Shin; Kubozono, Takuro; Sasaki, Yuichi; Ikeda, Yoshiyuki; Ohishi, Mitsuru; Miyahara, Hironori; Tokushige, Koichi
Abstract : Objective: Factors for New-Onset of isolated diastolic hypertension (IDH: systolic blood pressure ≧ 140 mmHg and diastolic blood pressure ≧ 90 mmHg) have been identified as increasing body mass index (BMI), young age at baseline, male, and BMI by analysis of the Framingham Study in middle-class Caucasians. However, in Japanese, there are few reports of predictors of IDH or the progression from IDH to systolic and diastolic hypertension (SDH: systolic blood pressure ≧ 140 mmHg and diastolic blood pressure ≧ 90 mmHg). Method: The present study analyzed 42, 591 subjects aged 35 to 65 years who underwent a health checkup between 2007 and 2013 and re-examined 5 years later. A logistic regression analysis was performed for three patterns of blood pressure change (normal to IDH, normal to SDH, and IDH to SDH) after 5 years from the time of the first health checkup. Systolic and diastolic blood pressure, age, gender, smoking habit, exercise habit, fasting blood glucose level, total cholesterol level, heart rate, and BMI were used as factors for adjustment. Results: At the time of the first checkup, 29, 965 subjects were normotensive, 1, 169 had IDH, and 11, 457 had SDH. Of the 29, 965 normotensive subjects, 566 developed IDH after 5 years. Multivariate logistic regression analysis adjusted for blood pressure showed a 1-unit increase in age (OR 0.96, CI[0.95–0.97], p < 0.0001), men (OR 1.44, CI[1.14–1.82], p = 0.002), BMI (OR 1.03, CI[1.00–1.06], p = 0.002), and a 1-unit increase in heart rate (OR 1.02, CI[1.01–1.03], p < 0.0001) were independently significant predictors of developing IDH. Of the 29, 965 normotensive subjects, 4, 631 developed SDH after 5 years, and all factors except heart rate were independently significant predictors. On the other hand, 612 (52%) of the 1, 169 subjects with IDH at the initial visit developed SDH 5 years later. The first checkup systolic blood pressure was significantly (p < 0.0001, 132.3 ± 5.5 mmHg vs. 129.5 ± 6.5 mmHg) higher, but no factors were found to be associated with the development of SDH. Conclusions: In Japanese subjects, IDH predominantly occurs in young, male, obese, and high heart rate individuals. However, the progression from IDH to SDH is difficult to predict, and it is important to prevent obesity from developing IDH.